Clinicopathological significance of ERCC1 expression in breast cancer - Gerhard, Renê; Carvalho, Ana; Carneiro, Vítor; Bento, Rui San; Uemura, Gilberto [UNESP]; Gomes, Madalena; Albergaria, André; Schmitt, Fernando (Elsevier, 2013)
The excision repair cross-complementation 1 (ERCC1) enzyme plays an essential role in the nucleotide excision repair pathway and is associated with resistance to platinum-based chemotherapy in different types of cancer. The aim of the present study was to evaluate the clinicopathological significance of ERCC1 expression in breast cancer patients. We analyzed the immunohistochemical expression of ERCC1 in a tissue microarray from 135 primary breast carcinomas and correlated the immunohistochemical findings with clinicopathological factors and outcome data. ERCC1 expression analysis was available for 109 cases. In this group, 58 (53.2%) were positive for ERCC1. ERCC1-positive expression was correlated with smaller tumor size (P=0.007) and with positivity for estrogen receptor (P=0.040), but no correlation was found with other clinicopathological features. Although not statistically significant, triple negative breast cancers were more frequently negative for ERCC1 (61.5% of the cases) compared to the non-triple negative breast cancer cases (41.5%). In conclusion, ERCC1 expression correlated significantly with favorable prognostic factors, such as smaller tumor size and ER-positivity, suggesting a possible role for ERCC1 as a predictive and/or prognostic marker in breast cancer. © 2013 Elsevier GmbH.
Keywords: Breast cancer; Breast cancer molecular subtypes; Excision repair cross-complementation 1; Immunohistochemistry; estrogen receptor; excision repair cross complementing protein 1; adult; carcinoma; excision repair; histopathology; human; immunohistochemistry; major clinical study; prognosis; protein expression; tissue microarray; triple negative breast cancer; tumor volume